Acid‐Catalyzed Synthesis of Diverse Indol‐3‐Yl‐Substituted Tetrahydropyridines through Three‐Component Reactions. Issue 16 (26th July 2022) - Zhu, Hongmei; Chen, Lei; Bai, Rongxian; Gu, Yanlong
Abstract: Two classes of indole‐tetrahydropyridine hybrid molecules were synthesized via three‐component reactions of: (i) 1‐amino‐3, 3‐diethoxypropane, diethyl acetylenedicarboxylate and indole; and (ii) ethyl 3‐aminocrotonate, acrolein and 2‐methylindoles. These one‐pot reactions provided straightforward ways to access indole‐tetrahydropyridine hybrid molecules with enriched molecular diversity. The reactions were most likely triggered by Michael addition, and the generated adducts were trapped by the indole component, leading to the formation of indol‐3‐ylimine intermediate. The obtained indol‐3‐yl‐substituted tetrahydropyridines could be converted into indole‐pyridine hybrid molecules with the aid of DDQ. Abstract :